Implementation of β-chaotic mapping to improved elephant herding optimisation to dynamic economic dispatch problem. (3rd June 2022) - Paramguru, Jagannath; Barik, Subrat Kumar
In this paper, a chaotic function is mapped to an improved novel swarm intelligence technique for performing a dynamic economic operation of conventional generators. Practical constraints like ramp rate limit, valve point loading effect and transmission losses are taken into account for the operation of the generators. This modified optimisation algorithm is proposed for solving the economic load dispatch problem based on the herding behaviour of the elephants under the leadership of the matriarch. Here, two-updating processes were involved for the optimum operation, which depend upon the response of each elephant in a clan and the separating behaviour of male elephant. The existing technique is mapped with a specified β-chaotic function to improve exploration and exploitation superiority. This proposed technique is applied and compared for four test system to find the dominance over other applied techniques. A comparative analysis is illustrated with other techniques for this proposed method to deduce the supremacy and enhancement.